2008
DOI: 10.1021/np070532u
|View full text |Cite
|
Sign up to set email alerts
|

Cucurbitane-Type Triterpenoids from the Stems of Momordica charantia

Abstract: Four new cucurbitane-type triterpenes, cucurbita-5,23(E)-diene-3beta,7beta,25-triol (1), 3beta-acetoxy-7beta-methoxycucurbita-5,23(E)-dien-25-ol (2), cucurbita-5(10),6,23(E)-triene-3beta,25-diol (5), and cucurbita-5,24-diene-3,7,23-trione (6), together with four known triterpenes, 3beta,25-dihydroxy-7beta-methoxycucurbita-5,23(E)-diene (3), 3beta-hydroxy-7beta,25-dimethoxycucurbita-5,23(E)-diene (4), 3beta,7beta,25-trihydroxycucurbita-5,23(E)-dien-19-al (7), and 25-methoxy-3beta,7beta-dihydroxycucurbita-5,23(E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 20 publications
3
40
0
Order By: Relevance
“…Bitter gourd and zucchini are known to contain a variety of biologically active compounds including the alkaloids momordicine I, momordicine II, and cucurbitacine B (Majekodunmi et al, 1990). Other compounds reported in these vegetables include a cytotoxic ribosome binding terpenoid and several glycosides including charantin, charantoside, and momordicoside (Begum et al, 1997;Harinantenaina et al, 2006;Akihisa et al, 2007;Chang et al, 2008;Dhiman et al, 2012). Glycosides are hydrolyzed by β-glucosidase enzymes (EC 3.2.1.21).…”
Section: Introductionmentioning
confidence: 99%
“…Bitter gourd and zucchini are known to contain a variety of biologically active compounds including the alkaloids momordicine I, momordicine II, and cucurbitacine B (Majekodunmi et al, 1990). Other compounds reported in these vegetables include a cytotoxic ribosome binding terpenoid and several glycosides including charantin, charantoside, and momordicoside (Begum et al, 1997;Harinantenaina et al, 2006;Akihisa et al, 2007;Chang et al, 2008;Dhiman et al, 2012). Glycosides are hydrolyzed by β-glucosidase enzymes (EC 3.2.1.21).…”
Section: Introductionmentioning
confidence: 99%
“…As part of our program aimed at the discovery of bioactive secondary metabolites from Taiwanese M. charantia, we had reported the isolation and structure elucidation of twenty-five cucurbitane-type triterpenoids from the MeOH extract of the stems of this plant. [18][19][20][21][22] In the continuing phytochemical investigation on M. charantia, we further identified one new ergostane sterol, 5a,6a-epoxy-3b-hydroxy-(22E,24R)-ergosta-8,22-dien-7-one (1), along with eight known sterols, 5a,6a-epoxy-(22E,24R)-ergosta-8,22-diene-3b,7a-diol (2), 23 5a,6a-epoxy-(22E,24R)-ergosta-8,22-diene-3b,7b-diol (3), 24 5a,6a-epoxy-(22E,24R)-ergosta-8(14),22-diene-3b,7a-diol (4), 23 3b-hydroxy-(22E,24R)-ergosta-5,8,22-trien-7-one (5), 25 ergosterol peroxide (6), 26 clerosterol (7), 27,28 decortinol (8), 27 and decortinone (9). 27 We describe in this paper the extraction, isolation, purification, and structure elucidation of compound 1 and the cytotoxic activity of compounds 1, 4, 5, 8, and 9.…”
Section: Introductionmentioning
confidence: 99%
“…Terpenes, a phytochemical present in M. charantia (Chang et al, 2008) have been reported to have antiproliferative effect (Akhisa et al, 2007). This suggests that terpenes contributed to the anti-proliferative effect of M. charantia observed on the cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%